2021
DOI: 10.4149/km_2019_5_307
|View full text |Cite
|
Sign up to set email alerts
|

The effects of welding speed on the microstructure and mechanical properties of marine-grade aluminium (AA5754) alloy welded using MIG welding

Abstract: AA5754 aluminium alloys are commonly used in marine and offshore applications as well as in shipbuilding equipment. It is of great importance to weld this alloy in these industrial areas. This study investigated the penetration, microstructure, and mechanical properties of AA5754 Al alloy sheets that were joined using robotic metal inert gas (MIG) welding at different welding speeds. The joints were welded at three welding speeds by keeping the welding current constant, and then macrostructure and microstructu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 15 publications
0
2
0
3
Order By: Relevance
“…Macroporous and mesoporous structures formed at the weld seams' foundations. Faster welding speeds exacerbated the problem by reducing the weld quality and negatively impacting the material's mechanical properties [25]. Tests for hardness and tensile strength showed that the material was marginally superior to the base metal.…”
Section: Introductionmentioning
confidence: 99%
“…Macroporous and mesoporous structures formed at the weld seams' foundations. Faster welding speeds exacerbated the problem by reducing the weld quality and negatively impacting the material's mechanical properties [25]. Tests for hardness and tensile strength showed that the material was marginally superior to the base metal.…”
Section: Introductionmentioning
confidence: 99%
“…For example, fusion-welded base materials have large deformation and thermal zones, which are prone to cracking [2]. In addition, ceramic materials or high temperature materials cannot be bonded with Al alloys [3], and the resultant porosity is inappropriate for a vacuum chamber material [4]. Fusion welding also has a slow welding speed and high cost [5]; in addition, only butt bonding, and not face-to-face bonding, can be performed, and reactive metals cannot be heterogeneously bonded [6].…”
Section: Introductionmentioning
confidence: 99%
“…MIG kaynak yönteminde argon (Ar), helyum (He) gazları ve farklı oranlarda karışım gazlar (Ar-He, Ar-CO2-O2, Ar-O2 v.s) kullanılabilmektedir. MAG kaynağında ise aktif bir gaz olan CO2 gazı kullanılmaktadır [24][25][26][27][28][29][30][31].…”
unclassified
“…Dolayısıyla kaynaklı birleştirmelerde ilk aranan özellik birleştirmenin dayanımının ana metal ile aynı veya ona yakın olmasıdır [3,15,[24][25][26][27]. Ancak kaynak işlemi sadece kaynak dikişinin kimyasal bileşimini değiştirmekle kalmaz, aynı zamanda termal döngüye maruz kalan ısıdan etkileyen bölgede bazı metalürjik değişiklikler meydana getirir [28][29][30][31][32]. Bu nedenle kaynak işlemi sonrası kaynak bölgesinin soğuma hızı bağlantıların mekanik ve metalurjik özelliklerini etkileyebilmektedir [26,27,33,34].…”
unclassified
See 1 more Smart Citation